Inferior dental nerve symptomatology in dental practice needs exclusion of sickle cell disease - Felix I D Konotey-Ahulu (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Sickle cell disease is defined as two abnormal beta-globin genes at least one of which is the sickle cell gene denoted by the capital letter S [1]. Other Abnormal beta-globin-genes are denoted either by capital letters of the alphabet C D E G K ... [2] or by the name of the place where the abnormal haemoglobin was found, for example, Haemoglobins Korle Bu [3], Osu-Christiansborg [4], K Woolwich [5] all of which are qualitative beta-globin gene abnormalities. There can, however, be a quantitative beta-globin gene abnormality which then is called beta-thalassemia and which I denote as beta-thal.